An Approach to One‐Pot Regioselective Synthesis of Indenones through Palladium‐Catalyzed Annulation in Water. Issue 30 (26th July 2018) - Ramesh, Karu; Satyanarayana, Gedu
Abstract : A one‐pot synthesis of indenones is presented. The process involves palladium‐catalyzed annulation of ortho ‐halobenzaldehydes with internal alkynes. Notably, it proceeded successfully in water as the sole, and green, solvent. Significantly, unlike in earlier reports, this protocol showed excellent regioselectivity with unsymmetrical alkylarylacetylenes. Further, the strategy was extended to a one‐pot synthesis of a neolignan natural product. Abstract : Functionalized indenones have been synthesized through domino Pd‐catalyzed annulation of ortho ‐halobenzaldehydes with internal alkynes with use of water as sole, and green, solvent. This protocol showed excellent regioselectivity with unsymmetrical alkylarylacetylenes and the strategy was extended to the synthesis of a neolignan natural product.